Impaired Higher-Level Functional Capacity as a Predictor of Stroke in Community-Dwelling Older Adults: The Ohasama Study. Issue 2 (February 2016) - Murakami, Keiko; Tsubota-Utsugi, Megumi; Satoh, Michihiro; Asayama, Kei; Inoue, Ryusuke; Ishiguro, Aya; Matsuda, Ayako; Kanno, Atsuhiro; Yasui, Daisaku; Murakami, Takahisa; Metoki, Hirohito; Kikuya, Masahiro; et al.
Abstract : Background and Purpose—: Functional capacity is a predictor, as well as a consequence, of stroke. However, little research has been done to examine whether higher-level functional capacity above basic activities of daily living is a predictor of stroke. Methods—: We followed 1493 Japanese community-dwelling adults aged ≥60 years (mean age, 70.1 years) who were independent in basic activities of daily living and had no history of stroke. Baseline data were collected using a self-administered questionnaire. Higher-level functional capacity was measured using the total score and 3 subscales (instrumental activities of daily living, intellectual activity, and social role) derived from the Tokyo Metropolitan Institute of Gerontology Index of Competence. Adjusted hazard ratios and 95% confidence intervals were calculated by the Cox proportional hazards model. Results—: During a mean follow-up of 10.4 years, 191 participants developed a first stroke. Impaired higher-level functional capacity based on total score of the Tokyo Metropolitan Institute of Gerontology Index of Competence was significantly associated with stroke (hazard ratio, 1.64; 95% confidence interval, 1.15–2.33). Among the 3 subscales, only intellectual activity was significantly associated with stroke (hazard ratio, 1.64; 95% confidence interval, 1.21–2.22). Social role was significantly associated with stroke only among those aged ≥75 years (hazard ratio, 1.78; 95% confidence interval, 1.07–2.98). Conclusions—: Impaired higher-level functional capacity, especially in the domain of intellectual activity, was a predictor of stroke, even among community-dwelling older adults with independent basic activities of daily living at baseline. Monitoring of higher-level functional capacity might be useful to detect those at higher risk of developing stroke in the future. Abstract : Supplemental Digital Content is available in the text.